Local Language Phonological Constraint-Based in Learning Pronunciation of English: An Experimental Study of English Department - Uswatun Hasanah; Nurahmadi; Arafiq; Nurachman (Journal of Classroom Action Research, 2023)
This study aims of finding out whether local language phonological constraint based is effective to help Bimanese English students of English department of university of Mataram in learning standard English pronunciation. The data were collected through questionnaire to 15 Bimanese English students as the respondents. The questionnaire contained 60 items which are categorized into linguistics kinds from words, phrases, and sentences. The test was assessing the student pronunciation of middle central vowel [ə] [ɜ] and alveolar step consonant [d] and [t] which are considered difficult fear the Bimanese speakers due to their absence in Bimanese phonological inventory. Deployment the questionnaire was conducted offline and the data collection was carried out online through Spada. The data analysis was carried out by using t-test by comparing the initial competence (pretest) and the final competence (posttest) of students between the experimental class and the control class. Based on the analysis, two conclusions were obtained. First, there are 7 students who obtained the high score from 60 to 66. There are also 7 students who obtained the middle score from 50 to 56 and 1 student who obtained the low score which is 40. From each problem sounds above, most of them are still difficult pronounce sound [t] and some of them are still moderate on sound [ə][ɜ][d]. Second, there are 9 students who obtain the high score from 80 to 93. There are also 4 students who achieved a score 70-78 and there are 2 students who got low score from 60 to 68. From the data above, there is a change in their pronunciation especially the sound problematic in English students so that they can achieve good scores.